Modifikasi Pembangkit Kunci Algoritma Vigenere Cipher Berdasarkan Pembangkit Bilangan Acak CSPRNG Untuk Mengamankan Citra Digital - Sianturi, Menanti; Zebua, Taroni Sokhi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The distribution of digital images in the current digital era is very rapid. The distribution of digital images has become a habit for every person every day, some are for public consumption and some are confidential. We can see the distribution of digital images in the use of social media, online shops, offices and government. Of course, everyone who distributes digital images does not want to lose the meaning of the digital image because people do bad work, or the digital image is misused by parties who do not have authority over the image, so it needs to be secured. Security issues have been an issue that has been discussed endlessly since the past until now. Information that is confidential, sensitive or of high value is kept secure so that it cannot be accessed by people who do not have authority over the information. Likewise with digital images, they must be safe from people who do not have authority over the image. Digital images can be secured using cryptographic algorithms. This research discusses how to modify the Vigenere cipher with a CSPRNG key generator based on the RSA algorithm. The Vigenere cipher is a classic cryptographic algorithm that utilizes key length as a strength to secure data and information. The longer the key applied, the more secure the encryption, and long keys must be random and unique. In this research, the key that will be used is a CSPRNG random number generator based on the RSA algorithm. The random numbers generated by this algorithm are believed to be very difficult for attackers to compute. By applying this algorithm to encrypt digital images, it is believed to be able to secure digital images, the pixel pattern in the image will be as random as possible. The transmitted digital image will be distributed in a random pixel pattern and will appear useless to attackers. The application of this algorithm is believed to be able to maintain digital image security.